Influence of 1-propanol/water ratio in catalyst inks for doctor-blade coated H2-PEMFC electrodes - Ayoub, Marc; Hübner, Christoph; Martschin, Philipp; Kerres, Jochen; Thiele, Simon; Brodt, Matthew (International Journal of Hydrogen Energy, 2025)
In this study, we vary the 1-propanol/water and ionomer/carbon (I/C) ratios in catalyst inks with a high total solid content of 10 wt%. The influence of the ratios on the inks is analyzed via the processing properties, while the resulting electrodes are characterized using electrochemical hydrogen fuel cell tests. The 1-propanol/water ratio variation showed a stronger effect on the rheological and wetting properties and thus the coating qualities for low I/C inks than for high I/C inks. Different void volume fractions and electrode thicknesses are observed for the various ionomer contents and alcohol concentrations for the coated electrodes. In some cases, primarily in low I/C inks, significant differences in proton conduction and mass transport properties are observed by detailed electrochemical analysis. For some ink formulations these differences counterbalance each other, resulting in minimal net differences in the polarization curves. As a result, the interplay between ionomer concentration and alcohol content is shown to be non-straightforward and significant for optimizing the formulations of high solid weight content inks.
CRIS-Team Scopus Importer:2025-05-30